Sex as an expression of hospitality - Theological investigation amongst some Africans - Baloyi, Elijah (2016)
Besides the fact that sexual relationships have been understood and misunderstood in different ways, the possibility of sexual abuse remains a big issue amongst African South Africans. It has been sexual relationships, amongst other factors that have been widely used to dominate one gender by the other. Sometimes because of their defencelessness women are perceived to enjoy the kind of sexual abuse they are subjected to. It is from attitude that some people, particularly men, come to the conclusion that sexual intercourse is another form of hospitality that can be offered to women. This kind of thinking has been fuelled by the traditional rejection of singlehood or widowhood and other related situations. It is for this reason that polygamy, levirate marriage and cohabitation have crept into the minds of some men. This paper will attempt to unveil how the thinking of sexual intercourse as hospitality has encouraged the domination and abuse of women in the African context. The study will also unveil how the gift of sex has been misunderstood and misinterpreted in order to subject women to sexual violence and harassment
Keywords: African Women; Domination; Equality; sex hospitality; Sexual Abuse